2014
DOI: 10.4304/tpls.4.2.287-292
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Attitude towards Using Cooperative Learning for Teaching Reading Comprehension

Abstract: Abstract-This study project was launched in order to contribute to the studies conducted for investigating the efficiency of different models of reading instruction. The aim of this paper was to investigate students' attitude towards using cooperative language learning techniques for reading instruction. Although cooperative methods are becoming more prevalent in private language schools, there are few studies regarding evaluating the students' attitude towards using cooperative learning for instructing readin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
42
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 12 publications
(9 reference statements)
10
42
1
Order By: Relevance
“…Assessment tools per Research Question (RQ) are presented below in Table 3. They appear in the literature [24][25][26][27][28][29] as they had been used in related studies. For the needs of this study, they had been slightly adapted (e.g., more specific questions have been added about the motion-based games and natural user interaction).…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessment tools per Research Question (RQ) are presented below in Table 3. They appear in the literature [24][25][26][27][28][29] as they had been used in related studies. For the needs of this study, they had been slightly adapted (e.g., more specific questions have been added about the motion-based games and natural user interaction).…”
Section: Data Collectionmentioning
confidence: 99%
“…For the needs of this study, they had been slightly adapted (e.g., more specific questions have been added about the motion-based games and natural user interaction). • Final student's questionnaire [28,29] • Final teacher's questionnaire [28,29] RQ2: Was the proposed educational approach implemented successfully and as planned in the school environments?…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, in order to encourage high achievement in English language, it is recommended that teachers structurally plan their teaching and learning activities in order to maximize the practice of student-centred learning activities in their daily lessons. Nima Farzaneh (2014) in her findings suggested that cooperative learning approach be employed for skills like reading comprehension because cooperative learning collect suggestions and ideas from different group members and helps the understanding of concepts become easily clear.…”
Section: Conclusion and Recommendationmentioning
confidence: 99%
“…The benefit of having positive attitudes towards student-centred learning practices is that when students work together in groups they feel that they can depend on others for help and this gives them the confidence to solve problems and enjoy learning. According to Nima Farzaneh (2014), positive attitudes on student-centred learning approaches may indirectly change the students' attitude towards language learning and encourage students' interest.…”
Section: The Importance Of Teachers' Teaching Beliefs and Attitudesmentioning
confidence: 99%